2014
DOI: 10.1089/ars.2014.5940
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbaric Oxygen, Vasculogenic Stem Cells, and Wound Healing

Abstract: Significance: Oxidative stress is recognized as playing a role in stem cell mobilization from peripheral sites and also cell function. Recent Advances: This review focuses on the impact of hyperoxia on vasculogenic stem cells and elements of wound healing. Critical Issues: Components of the wound-healing process in which oxidative stress has a positive impact on the various cells involved in wound healing are highlighted. A slightly different view of woundhealing physiology is adopted by departing from the oft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
70
0
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(83 citation statements)
references
References 183 publications
0
70
0
8
Order By: Relevance
“…Using supplemental oxygen, the choroidal vessels can supply sufficient oxygen to the inner layers of the retina by diffusion, maintaining ganglion cell viability even when the retinal vessels have been completely obliterated 30. HBOT incorporates the inhalation of 100% oxygen at pressures exceeding 1 ATA, thus increasing the amount of oxygen dissolved in the plasma 20–30 times 12. Normally, under normoxic conditions, approximately 60% of the retina’s oxygen consumption is supplied from the choroidal circulation, whereas, under such hyperoxic conditions, the choroid is capable of supplying 100% of the oxygen needed by the retina 31…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using supplemental oxygen, the choroidal vessels can supply sufficient oxygen to the inner layers of the retina by diffusion, maintaining ganglion cell viability even when the retinal vessels have been completely obliterated 30. HBOT incorporates the inhalation of 100% oxygen at pressures exceeding 1 ATA, thus increasing the amount of oxygen dissolved in the plasma 20–30 times 12. Normally, under normoxic conditions, approximately 60% of the retina’s oxygen consumption is supplied from the choroidal circulation, whereas, under such hyperoxic conditions, the choroid is capable of supplying 100% of the oxygen needed by the retina 31…”
Section: Discussionmentioning
confidence: 99%
“…During HBOT treatment, the arterial O 2 tension typically exceeds 2,000 mmHg 12. The proposed role for hyperbaric oxygen in CRAO is to increase the oxygen delivery to the ischemic tissue until spontaneous or assisted reperfusion occurs.…”
Section: Introductionmentioning
confidence: 99%
“…People with hard to heal DFUs can often be characterized by the presence of microvascular disease and having impaired bacterial killing capacity as well as reduced stem cell mobilization. Many preclinical and animal studies have shown that HBO stimulates angiogenesis, reduces edema, augments granulation tissue formation by enhancing fibroblasts, improves leukocyte function, and mobilizes stem cells from the bone marrow . In people with hard‐to‐heal DFUs, HBO increases transcutaneous oxygen (TcPO 2 ) levels in the feet and TcPO 2 levels are associated with treatment outcomes .…”
Section: Promentioning
confidence: 99%
“…During HBOT treatment, the arterial O 2 tension typically exceeds 2000 mmHg, and levels of 200-400 mmHg occur in tissues [121]. The most common clinical uses of HBOT are for non-healing wounds and radiation-related injuries.…”
Section: Hyperbaric Oxygen Therapy (Hbot)mentioning
confidence: 99%